THE EFFECTIVENESS OF PORPE STRATEGY IN TEACHING READING COMPREHENSION TO THE ELEVENTH GRADE STUDENTS OF SMA YAYASAN BAKTI PRABUMULIH - Asti Veto Mortini; Aswadi Jaya (Universitas PGRI Palembang, 2019)
Abstract: PORPE is a study strategy that can be used in any content area course that uses the essay exam to measure learning or any test format that encourages higher levels of thinking such as synthesis, application, and evaluation. This study was conducted as an attempt to find out the effectiveness of applying Predict, Organize, Rehearse, Practice, Evaluate (PORPE) strategy on students’ reading comprehension. This study used experimental design. The population of this studywas students of Grade XI, Senior High School Yayasan Bakti Prabumulih which consisted of 120 students. There were sixty students from the population taken as the sample in this study. The sample was divided into two randomized groups: experimental and control groups . The experimental group was taught by using PORPE strategy, while the control group was taught by using conventional method. To obtain the reliability of the test, the writer applied Kuder Richardson 21 formula (KR- 21) . The result of the reliability was 0.81. The data were analyzed by using t-test formula. The analysis showed that the scores of the students in the experimental group were significantly higher than the scores of the students in the control group at the level of significance 0.05 with the degree of freedom (df) 58 , t -observed value 2.8 > t – table value 2.00. The findings indicated that using PORPE strategy significantly affected the students’ reading com prehension. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted.